CORRELATION OF THE PRESENCE OF SYMPTOMS ASSOCIATED WITH TEMPOROMANDIBULAR DYSFUNCTION WITH ACTIVATION OF THE TEMPORAL AND MASSETER MUSCLES (Fiep Bulletin - online, 2014)
For a proper functioning of the temporomandibular joint (TMJ) is both necessary harmony between the ATM itself, as the dental occlusion and neuromuscular balance. The term temporomandibular disorder (TMD) is used to describe a group of diseases that involve the masticatory muscles, TMJ and surrounding structures. The aim of this study was to correlate the presence of symptoms associated with TMD activation of temporal and masseter muscles bilaterally by EMG. The sample consisted of 20 women, aged 20 to 25 years, presenting signs and symptoms of TMD according to the Index of Anamnesic FONSECA. Dual surface electrodes were placed on the masseter and temporalis muscles on both sides. The EMG recordings were performed with maximum voluntary contraction with gauze between the teeth for 5 seconds. The indices of surface electromyography were correlated with the values ??of the questionnaire Anamnesic Index of Fonseca, by Pearson correlation, with significance level of 5%. No significant correlations were found between the variables of muscle activation and the IAF. The results indicated no correlation between activation of masticatory muscles in the presence of symptoms associated with TMD.
Keywords: Temporomandibularjoint; Temporomandibular Joint Disorders; electromyography